Sphingolipids and Inositol Phosphates Regulate the Tau Protein Phosphorylation Status in Humanized Yeast - Randez-Gil, Francisca; Bojunga, Lino; Estruch, Francisco; Winderickx, Joris; Del Poeta, Maurizio; Prieto, Jose A. (Frontiers in Cell and Developmental Biology, 2020)
Hyperphosphorylation of protein tau is a hallmark of Alzheimer’s disease (AD). Changes in energy and lipid metabolism have been correlated with the late onset of this neurological disorder. However, it is uncertain if metabolic dysregulation is a consequence of AD or one of the initiating factors of AD pathophysiology. Also, it is unclear whether variations in lipid metabolism regulate the phosphorylation state of tau. Here, we show that in humanized yeast, tau hyperphosphorylation is stimulated by glucose starvation in coincidence with the downregulation of Pho85, the yeast orthologue of CDK5. Changes in inositol phosphates (IPs) signaling, which has a central role in energy metabolism, altered tau phosphorylation. Lack of inositol hexakisphosphate kinases Kcs1 and Vip1 (IP6 and IP7 kinases in mammals) increased tau hyperphosphorylation. Similar effects were found by mutation of IPK1 (inositol-pentakisphosphate 2-kinase), or PLC1, the yeast phospholipase C gene. These effects may be explained by IPs-mediated regulation of Pho85. Indeed, this appeared to be the case for kcs1 and plc1. However, the effects of Ipk1 or Vip1 on tau phosphorylation were independent of the presence of Pho85, suggesting additional mechanisms. Interestingly, kcs1 and vip1 strains, like pho85, displayed dysregulated sphingolipids (SLs) metabolism. Moreover, genetic and pharmacological inhibition of SLs biosynthesis stimulated the appearance of hyperphosphorylated forms of tau, while increased flux through the pathway reduced its abundance. Finally, we demonstrated that Sit4, the yeast orthologue of human PP2A protein phosphatase, is a downstream effector of SLs signaling in mediating the tau phosphorylation state. Altogether, our results add new knowledge on the molecular mechanisms involved in tauopathies and identify new targets for pharmacological intervention.